Mountains and molehills; or, Recollections of a burnt journal - Marryat, Frank, 1826-1855.; Trask, John B. (John Boardman), 1824-1879. (New York, Harper & brothers, 1855)
Frank Marryat (1826-1855) left England for California via Panama with a manservant and three hunting dogs in 1850, hoping to find material for a book like his earlier Borneo. On his return to England in 1853, Marryat married and brought his bride back to California that same year. Yellow fever contracted on shipboard forced him to cut the trip short and return to England where he died two years later. Mountains and molehills (1855) is a sportsman-tourist's chronicle of California in the early 1850s: hunting, horse races, bear and bull fights. It also includes an Englishman's bemused comments on social life in San Francisco, Stockton, and the gold fields.
"Extracts from a work by Dr. J.B. Trask ... on the geology of California": p. [383]-393.
Also available in digital form on the Library of Congress Web site.
Keywords: California -- Description and travel; California -- Gold discoveries; Geology -- California; Ethnic groups -- California; Law -- Political aspects -- California; Mines and mineral resources -- California